2016
DOI: 10.1111/ctr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Recreational marijuana use is not associated with worse outcomes after renal transplantation

Abstract: As marijuana (MJ) legalization is increasing, kidney transplant programs must develop listing criteria for marijuana users. However, no data exist on the effect of MJ on kidney allograft outcomes, and there is no consensus on whether MJ use should be a contraindication to transplantation. We retrospectively reviewed 1225 kidney recipients from 2008 to 2013. Marijuana use was defined by positive urine toxicology screen and/or self-reported recent use. The primary outcome was death at 1 year or graft failure (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 34 publications
(38 reference statements)
3
53
1
Order By: Relevance
“…Since California permitted the use of medical marijuana in 1996, followed by recreational legalization in the states of Washington and Colorado in 2012, there have been multiple studies evaluating its safety. Our study has shown, as have others, that marijuana should not be the sole reason to exclude a patient from transplantation because these patients have similar longterm outcomes and graft and patient survival as nonusers in both liver and kidney transplantation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Since California permitted the use of medical marijuana in 1996, followed by recreational legalization in the states of Washington and Colorado in 2012, there have been multiple studies evaluating its safety. Our study has shown, as have others, that marijuana should not be the sole reason to exclude a patient from transplantation because these patients have similar longterm outcomes and graft and patient survival as nonusers in both liver and kidney transplantation.…”
Section: Discussionsupporting
confidence: 73%
“…Medical marijuana has been successfully used to treat pruritus, chronic pain, depression, anorexia, sleep disturbance, and nausea, which are all symptoms that are consistently reported by pretransplant patients . However, neither medical marijuana nor recreational marijuana is regulated for purity or potency, leaving users potentially vulnerable to unpredictable medical efficacy and adverse effects.…”
mentioning
confidence: 99%
“…The long‐term risk of medical cannabis use in renal transplant patients was examined recently by Greenan et al In a retrospective review of 1225 renal transplant recipients, the researchers found medical cannabis use was not associated with poorer patient or kidney allograft outcomes at 1 year. The primary outcome of survival at 1‐year post‐transplant did not differ between users and non‐users (100% vs 97.7%; P = 0.622).…”
Section: Concerns Voiced By the Transplant Teammentioning
confidence: 99%
“…Renal allograft is typically classified as deceased-donor or living-donor transplantation depending on the source of the donor organ. [1] According to the Organ Procurement and Transplant Network (OPTN) records, nearly 85,000 candidates were on the waiting list for kidney transplantation in 2010, and ≈17,700 kidney transplantations (including 828 kidneypancreas transplantations) were performed. [2] The data from the United States Renal Data System (USRDS) shows that currently approximately one in three donations is from a live donor.…”
Section: Introductionmentioning
confidence: 99%